2022
DOI: 10.4269/ajtmh.21-0591
|View full text |Cite
|
Sign up to set email alerts
|

Financial Incentives, Not Behavioral Nudges, Led to Optimized HIV Testing among Pregnant Women in a High-Burden Urban Population in Ecuador

Abstract: Behavioral economic principles are increasingly being used in the fight against HIV, including improving voluntary testing in sub-Saharan Africa and South America. However, behavioral nudges have not been widely tested as a strategy to optimize HIV testing in pregnant women. Here, we assessed whether behavioral nudges or financial incentives were effective in optimizing HIV testing among pregnant women in a high-HIV burden setting. A randomized clinical trial was conducted between May 21 and Oct 5, 2018, to al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
0
0
Order By: Relevance
“…A unique approach was explored in an RCT by Ortiz et al., 49 which tested the impact of financial incentives on antenatal HIV screening decisions. The study found a significant increase in screening rates when participants were offered a monetary incentive.…”
Section: Resultsmentioning
confidence: 99%
“…A unique approach was explored in an RCT by Ortiz et al., 49 which tested the impact of financial incentives on antenatal HIV screening decisions. The study found a significant increase in screening rates when participants were offered a monetary incentive.…”
Section: Resultsmentioning
confidence: 99%